Polishing Pad

JP7645623B2Active Publication Date: 2025-03-14FUJIBO HLDG
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020165755
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-30
Publication Date
2025-03-14
Estimated Expiration
2040-09-30

AI Technical Summary

Benefits of technology

【0011】 本発明の研磨パッドによれば、研磨層の物性·気泡構造を変更することなく、端部ダレが抑制され、安定した研磨を実施することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007645623000005
    Figure 0007645623000005
  • Figure 0007645623000006
    Figure 0007645623000006
  • Figure 0007645623000007
    Figure 0007645623000007
Patent Text Reader

Abstract

To provide a polishing pad that can improve sagging of an end part, without changing a physical property / bubble structure of a polishing layer.SOLUTION: A polishing pad 3 comprises a polishing layer 4 having a polishing surface for polishing an object to be polished. In the polishing surface are provided a slurry holding groove formed in a shape for holding slurry and a slurry ejection groove formed in a shape for ejecting slurry. A ratio of mass of the slurry ejection groove to mass of the slurry holding groove (ejection groove mass / holding groove mass) is 0.5-1.0.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing pad. In particular, the present invention relates to a polishing pad that can be suitably used for polishing optical materials, semiconductor wafers, semiconductor devices, hard disk substrates, and the like. [Background technology]

[0002] Chemical mechanical polishing (CMP) is commonly used as a polishing method for planarizing the surfaces of optical materials, semiconductor wafers, semiconductor devices, and hard disk substrates.

[0003] The CMP method will be described with reference to FIG. 1. As shown in FIG. 1, a polishing apparatus 1 for carrying out the CMP method is provided with a polishing pad 3, which contacts an object 8 to be polished held on a holding platen 16 and includes a polishing layer 4, which is a layer for polishing, and a cushion layer 6 for supporting the polishing layer 4. The polishing pad 3 is rotated while the object 8 to be polished is pressed against it, and polishes the object 8 to be polished. At that time, a slurry 9 is supplied between the polishing pad 3 and the object 8 to be polished. The slurry 9 is a mixture (dispersion liquid) of water, various chemical components, and hard fine abrasive grains, and the chemical components and abrasive grains in the slurry are flowed and move relative to the object 8 to increase the polishing effect. The slurry 9 is supplied to the polishing surface through grooves or holes and discharged.

[0004] Incidentally, the polishing pad 3 has conventionally been one in which the polishing layer 4 is made of foamed polyurethane, but the polishing layer 4 follows the shape of the edge of the workpiece 8 during polishing, and an over-polishing phenomenon called "edge sagging" (8a in FIG. 2) occurs, in which the edge of the workpiece 8 is polished more than the center, as shown in FIG. 2. In addition, in order to eliminate the "edge sagging," the pressure of the retainer ring can be adjusted, but in this case, the pressure responsiveness of the polishing pad 3 becomes a problem. In other words, if a polishing pad 3 with low pressure responsiveness is used, it is not possible to adjust the polishing rate of the edge. In FIG. 4, which shows the polishing rate (RR) on the vertical axis and the distance on the straight line passing through the center of the workpiece 8 on the horizontal axis ("0" on the horizontal axis is the center of the workpiece), for a workpiece polished by a polishing pad of the prior art, it can be seen that the polishing rate at both ends is higher than the other parts, and edge sagging occurs. This edge sagging can be a problem in semiconductor polishing (especially in the process of polishing oxide films), especially when the polishing rate at the outermost edge (periphery) of the workpiece is 1.5 times or more higher than that of other parts of the workpiece.

[0005] In response to this over-polishing phenomenon known as edge sagging, Patent Document 1 discloses a polishing pad that prevents edge sagging while suppressing the occurrence of polishing scratches by controlling the hardness of the polishing layer within a certain range through the use of a specific bubble structure in the foam.

[0006] Patent Document 2 discloses a polishing pad that does not have the problem of edge sagging by setting the hardness and tear strength of the polishing layer within a specific range. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2012-714 A [Patent Document 2] JP 2016-190313 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, the polishing pads described in Patent Documents 1 and 2 above require specific physical properties and cell structures of the polishing layer, and even if the edge sagging can be improved, other polishing performance may be inferior.

[0009] The present invention has been made in consideration of the above problems, and aims to provide a polishing pad that makes it possible to improve edge sagging without changing the physical properties or cell structure of the polishing layer. [Means for solving the problem]

[0010] As a result of intensive research, the present inventors have discovered a polishing pad that can improve edge sagging by providing specific grooves in the polishing layer. [1] A polishing pad having a polishing layer having a polishing surface for polishing an object to be polished, the polishing surface is provided with a slurry retaining groove having a shape for retaining a slurry, and a slurry discharge groove having a shape for discharging the slurry; The polishing pad, wherein the ratio of the volume of the slurry retaining groove to the volume of the slurry discharge groove (discharge groove volume / retaining groove volume) is 0.5 to 1.0. [2] The polishing pad according to [1], wherein the groove width ratio (discharge / retention) between the slurry retaining groove and the slurry discharge groove is 1.5 to 7.5. [3] The polishing pad according to [1] or [2], wherein the groove pitch ratio (discharge / retention) between the slurry retaining grooves and the slurry discharge grooves is 4.5 to 15. [4] The polishing pad according to any one of [1] to [3], wherein hollow microspheres are dispersed on the polishing surface. Effect of the Invention

[0011] According to the polishing pad of the present invention, sagging at the edges is suppressed without changing the physical properties and cell structure of the polishing layer, and stable polishing can be performed. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a perspective view of a polishing apparatus 1. As shown in FIG. [Diagram 2] FIG. 2 is a side view of the workpiece 8 to be polished, showing the edge sagging. [Diagram 3] FIG. 3(a) is a perspective view and (b) is a cross-sectional view of a polishing pad 3 of the present invention. [Figure 4] FIG. 4 shows a profile of the polishing rate of the entire object 8 polished by the conventional technique (the polishing pad of Comparative Example 1) along a straight line passing through the center of the object 8. [Diagram 5] FIG. 5 shows the pressure response of the edge portion of an object 8 polished by the conventional technique (the polishing pad of Comparative Example 1). [Figure 6] FIG. 6 shows concentric grooves (FIG. 6(a)) and perforations (FIG. 6(b)), which are examples of slurry retaining grooves. [Figure 7] FIG. 7 shows examples of slurry discharge grooves, including a lattice groove (FIG. 7(c)), a radial groove (FIG. 7(d)), and a spiral groove (FIG. 7(e)). [Figure 8] FIG. 8 is a cross-sectional view of the polishing layer 3 near the polishing surface, where (a) shows a groove with a square cross section, and (b) shows a groove with a V-shaped cross section. [Figure 9] FIG. 9 shows the distance in a groove 10, where α is the land width of the groove, β is the groove width, and γ is the pitch width. [Figure 10] FIG. 10 shows a profile of the polishing rate of the entire object 8 polished using the polishing pad of Example 1 along a straight line passing through the center of the object 8. As shown in FIG. [Figure 11] FIG. 11 shows the pressure response of the edge portion of the object 8 polished by the polishing pad of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, a mode for carrying out the invention will be described, however, the present invention is not limited to the mode for carrying out the invention.

[0014] <<Polishing pad>> The structure of the polishing pad 3 will be described with reference to Fig. 3. As shown in Fig. 3, the polishing pad 3 includes a polishing layer 4 and a cushion layer 6. The shape of the polishing pad 3 is preferably disc-shaped, but is not particularly limited, and the size (diameter) can also be appropriately determined depending on the size of the polishing apparatus 1 equipped with the polishing pad 3, and can be, for example, about 10 cm to 2 m in diameter. In the polishing pad 3 of the present invention, the polishing layer 4 is preferably bonded to the cushion layer 6 via an adhesive layer 7 as shown in FIG. The polishing pad 3 is attached to a polishing platen 10 of the polishing device 1 by double-sided tape or the like arranged on the cushion layer 6. The polishing pad 3 is rotated by the polishing device 1 while being pressed against an object 8 to be polished, and polishes the object 8 to be polished.

[0015] <Polishing layer> (composition) The polishing pad 3 includes a polishing layer 4 that is a layer for polishing an object to be polished 8. The material constituting the polishing layer 4 can be suitably selected from polyurethane resin, polyurea resin, and polyurethane-polyurea resin, and more preferably polyurethane resin. The size (diameter) of the polishing layer 4 is the same as that of the polishing pad 3 and can be about 10 cm to 2 mm in diameter, and the thickness of the polishing layer 4 can usually be about 1 to 5 mm. The polishing layer 4 is rotated together with the polishing platen 10 of the polishing device 1, and while a slurry 9 is poured onto it, the chemical components and abrasive grains contained in the slurry 9 are moved relative to the object 8 to be polished, thereby polishing the object 8 to be polished. The polishing layer 4 has hollow microspheres 4A (foamed) dispersed therein. The dispersion of hollow microspheres 4A is preferable in that it allows the Shore D hardness to be adjusted to an appropriate value. Furthermore, because the hollow microspheres 4A are dispersed therein, when the polishing layer 4 is worn, the hollow microspheres 4A are exposed on the polishing surface, generating minute voids on the polishing surface. These minute voids hold the slurry, allowing the polishing of the object 8 to proceed more rapidly.

[0016] (groove) In the present invention, grooves 5 are provided by groove processing on the surface of the polishing layer 4 facing the polished object 8. The present invention is characterized in that the polishing surface of the polishing layer is provided with both slurry retaining grooves 5A and slurry discharging grooves 5B. Each of these will be described below.

[0017] The slurry holding groove 5A is a groove for holding the slurry, and the end is not connected to the end of the polishing layer, but is an independent groove. For example, the concentric groove shown in FIG. 6(a) and the perforation (through hole) shown in FIG. 6(b) are included. The slurry holding groove 5A is intended to hold the slurry and improve the polishing performance, and the provision of the slurry holding groove 5A can improve the ability to hold the slurry between the polishing pad 1 and the polished object 8.

[0018] The slurry discharge grooves 5B are grooves for discharging the slurry, and each groove is connected to an end of the polishing layer 8, and has an open end. For example, the grooves may be a lattice groove as shown in Fig. 7(c), a radial groove as shown in Fig. 7(d), or a spiral groove as shown in Fig. 7(e). The slurry discharge grooves 5B are intended to discharge the slurry, and by providing the slurry discharge grooves 5B, it becomes possible to constantly polish with fresh slurry.

[0019] In the present invention, one of the characteristics is that the ratio of the volume of the slurry holding groove 5A to the volume of the slurry discharge groove 5B (slurry discharge groove volume / slurry holding groove volume) is 0.5 to 1.0. In the calculation of the volume, if the cross section of FIG. 8(a) is a rectangular groove, the product of the area of ​​the rectangular cross section and the length of the groove is one groove volume, and the volume of the slurry holding groove of the polishing layer 3 is the total value of the volumes of the slurry holding grooves provided in the polishing layer 3. The same is considered for the slurry discharge groove. In addition, as shown in FIG. 8(b), when the cross section of the groove is V-shaped, the product of the area of ​​the triangle and the length of the groove is one groove volume. In FIG. 8, the cross-sectional area is the area of ​​X1, X2, and X3 in FIG. 8(a), and the area of ​​Y1, Y2, and Y3 in FIG. 8(b). The cross-sectional shape can also be applied to other shapes (for example, U-shaped, semicircular).

[0020] As described above, by setting the slurry discharge groove volume / slurry retention groove volume to a specific value, it becomes possible to suppress the occurrence of end sagging.

[0021] Furthermore, the ratio of the groove width of the slurry holding groove to the groove width of the slurry discharge groove (groove width of the slurry discharge groove / groove width of the slurry holding groove) is preferably set to 1.5 to 7.5, and more preferably set to 2.5 to 6.5. Furthermore, the ratio of the groove pitch of the slurry holding groove to the groove pitch of the slurry discharge groove (groove pitch of the slurry discharge groove / groove pitch of the slurry holding groove) is preferably set to 4.5 to 15, and more preferably set to 5.5 to 12.5. By setting the groove width of the slurry discharge groove / groove width of the slurry holding groove in the range of 1.5 to 7.5, and / or the groove pitch of the slurry holding groove and the groove pitch of the slurry discharge groove / groove pitch of the slurry holding groove in the range of 4.5 to 12.5, the end sagging is more unlikely to occur.

[0022] The groove width means the width of the groove, and is β in Fig. 9. The groove pitch means the distance from the end of a groove to the end of the same side of the adjacent groove, and is γ in Fig. 9. The α is the width excluding the grooves, and is the part called the land width.

[0023] (Shore D hardness) The Shore D hardness of the polishing layer 4 of the present invention is not particularly limited, but is, for example, 20 to 100, preferably 30 to 80, and more preferably 40 to 70. If the Shore D hardness is low, it becomes difficult to flatten fine irregularities by low-pressure polishing. In addition, it may affect edge sagging. If the Shore D hardness is too high, the polishing object 8 may be rubbed strongly against the polishing object 8, causing scratches on the processed surface of the polishing object 8.

[0024] The polishing layer 4 is formed by casting a mixture of an isocyanate group-containing compound mixed with hollow microspheres (described later) and a curing agent (chain extender), and slicing the cured foam. That is, the polishing layer 4 is dry molded.

[0025] In the polishing pad of the present invention, hollow microspheres 4A are used to encapsulate air bubbles inside the polyurethane resin molding. The hollow microspheres refer to microspheres having voids. The hollow microspheres include those having a spherical shape, an elliptical shape, and shapes similar thereto. Examples include those of a pre-expanded type and those of a non-expanded heat-expandable microsphere that is heat-expanded.

[0026] The physical properties of the abrasive layer 4, such as the Shore D hardness, can be adjusted to a desired range by adjusting the composition of the abrasive layer 4, the number and size of the hollow microspheres 4A, and the like.

[0027] <Cushion layer> (composition) The polishing pad 3 of the present invention has a cushion layer 6. It is desirable for the cushion layer 6 to make the polishing layer 4 contact the polished object 8 more uniform. The material of the cushion layer 6 may be any of impregnated nonwoven fabric impregnated with resin, flexible materials such as synthetic resins and rubbers, and foams having a cellular structure. Examples of the material include resins such as polyurethane, polyethylene, polybutadiene, and silicone, and rubbers such as natural rubber, nitrile rubber, and polyurethane rubber. From the viewpoint of adjusting the density and compressive elastic modulus, flexible synthetic resins are preferred, and polyurethane is preferably used as the material.

[0028] <Adhesive layer> The adhesive layer 7 is a layer for adhering the cushion layer 6 and the polishing layer 4, and is usually made of a double-sided tape or adhesive. The double-sided tape or adhesive may be any known double-sided tape or adhesive in the art (e.g., an adhesive sheet). The polishing pad 3 and the cushion layer 6 are bonded together by an adhesive layer 7. The adhesive layer 7 can be made of at least one adhesive selected from, for example, acrylic, epoxy, and urethane adhesives. In this example, an acrylic adhesive is used, and the thickness is set to 0.1 mm.

[0029] <<Polishing pad manufacturing method>> A method for producing the polishing pad 3 of the present invention will now be described.

[0030] <Abrasive layer material> The material of the polishing layer is not particularly limited, but is preferably a commonly used material, that is, a material having a polyurethane resin, a polyurea resin, or a polyurethane polyurea resin as a main component, and more preferably a polyurethane resin. A specific example of the main component material is a material obtained by reacting a urethane bond-containing polyisocyanate compound with a curing agent.

[0031] A method for producing the material of the polishing layer 4 will be described below using an example in which a urethane bond-containing isocyanate compound, a polyol compound, and a curing agent are used.

[0032] Examples of a method for producing the polishing layer 4 using a urethane bond-containing polyisocyanate compound and a curing agent include a production method including: a material preparation step of preparing at least a urethane bond-containing polyisocyanate compound, an additive, and a curing agent; a mixing step of mixing at least the urethane bond-containing polyisocyanate compound, the additive, and the curing agent to obtain a mixed liquid for molding a molded body; and a curing step of molding the mixed liquid for molding a molded body into a polishing layer.

[0033] The material preparation process, the mixing process, and the molding process will be explained below.

[0034] <Material preparation process> To manufacture the polishing layer 4 of the present invention, a urethane bond-containing polyisocyanate compound and a curing agent are prepared as raw materials for a polyurethane resin molded body (cured resin). Here, the urethane bond-containing polyisocyanate is a urethane prepolymer for forming a polyurethane resin molded body. When the polishing layer 4 is to be a polyurea resin molded body or a polyurethane-polyurea resin molded body, a prepolymer appropriate for the purpose is used.

[0035] Each component will be described below.

[0036] (Polyisocyanate compound containing urethane bonds) The urethane bond-containing polyisocyanate compound (urethane prepolymer) is a compound obtained by reacting the following polyisocyanate compound with a polyol compound under commonly used conditions, and contains a urethane bond and an isocyanate group in the molecule. In addition, other components may be contained in the urethane bond-containing polyisocyanate compound within the range that does not impair the effects of the present invention.

[0037] The urethane bond-containing polyisocyanate compound may be a commercially available product, or may be a product synthesized by reacting a polyisocyanate compound with a polyol compound. The reaction is not particularly limited, and addition polymerization may be performed using a method and conditions known in the production of polyurethane resins. For example, the polyisocyanate compound may be added to a polyol compound heated to 40°C while stirring in a nitrogen atmosphere, and the temperature may be raised to 80°C after 30 minutes, and the reaction may be continued at 80°C for 60 minutes.

[0038] (Polyisocyanate compounds) In this specification, the polyisocyanate compound means a compound having two or more isocyanate groups in the molecule. The polyisocyanate compound is not particularly limited as long as it has two or more isocyanate groups in the molecule. For example, diisocyanate compounds having two isocyanate groups in the molecule include m-phenylene diisocyanate, p-phenylene diisocyanate, 2,6-tolylene diisocyanate (2,6-TDI), 2,4-tolylene diisocyanate (2,4-TDI), naphthalene-1,4-diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), 4,4'-methylene-bis(cyclohexyl isocyanate) (hydrogenated MDI), 3,3'-dimethoxy-4,4'-biphenyl diisocyanate, 3,3'-dimethyl- Examples of the polyisocyanate include diphenylmethane-4,4'-diisocyanate, xylylene-1,4-diisocyanate, 4,4'-diphenylpropane diisocyanate, trimethylene diisocyanate, hexamethylene diisocyanate, propylene-1,2-diisocyanate, butylene-1,2-diisocyanate, cyclohexylene-1,2-diisocyanate, cyclohexylene-1,4-diisocyanate, p-phenylene diisothiocyanate, xylylene-1,4-diisothiocyanate, ethylidine diisothiocyanate, etc. These polyisocyanate compounds may be used alone or in combination of a plurality of polyisocyanate compounds.

[0039] The polyisocyanate compound preferably contains 2,4-TDI and / or 2,6-TDI, more preferably contains 2,4-TDI and 2,6-TDI, and even more preferably consists of 2,4-TDI and 2,6-TDI. The mass ratio of 2,4-TDI to 2,6-TDI is preferably 100:0 to 50:50, more preferably 90:10 to 60:40, even more preferably 90:10 to 70:30, and even more preferably 80:20.

[0040] (Polyol compounds as raw materials for prepolymers) In this specification, the polyol compound means a compound having two or more hydroxyl groups (OH) in the molecule. Examples of polyol compounds used in the synthesis of the urethane bond-containing polyisocyanate compound as a prepolymer include diol compounds, triol compounds, etc., such as ethylene glycol, diethylene glycol (DEG), butylene glycol, etc.; and polyether polyol compounds, such as poly(oxytetramethylene) glycol (or polytetramethylene ether glycol) (PTMG). Among these, PTMG is preferred. The number average molecular weight (Mn) of PTMG is preferably 500 to 2000, more preferably 600 to 1300, and even more preferably 650 to 1000. The number average molecular weight can be measured by gel permeation chromatography (GPC). When measuring the number average molecular weight of a polyol compound from a polyurethane resin, it can also be estimated by GPC after decomposing each component by a conventional method such as amine decomposition. The above polyol compounds may be used alone or in combination of two or more.

[0041] (Additives) As described above, additives such as an oxidizing agent can be added to the material of the polishing layer 4, if necessary.

[0042] (hardening agent) In the method for producing the polishing layer 4 of the present invention, a curing agent (also called a chain extender) is mixed with a urethane bond-containing polyisocyanate compound, etc. in a mixing step. By adding the curing agent, in the subsequent molding step, the main chain terminal of the urethane bond-containing polyisocyanate compound bonds with the curing agent to form a polymer chain, which then hardens. Examples of the curing agent include ethylenediamine, propylenediamine, hexamethylenediamine, isophoronediamine, dicyclohexylmethane-4,4'-diamine, 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), 4-methyl-2,6-bis(methylthio)-1,3-benzenediamine, 2-methyl-4,6-bis(methylthio)-1,3-benzenediamine, 2,2-bis(3-amino-4-hydroxyphenyl)propane, 2,2-bis[3-(isopropylamino)-4- polyamine compounds such as 2,2-bis[3-(1-methylpropylamino)-4-hydroxyphenyl]propane, 2,2-bis[3-(1-methylpentylamino)-4-hydroxyphenyl]propane, 2,2-bis(3,5-diamino-4-hydroxyphenyl)propane, 2,6-diamino-4-methylphenol, trimethylethylene bis-4-aminobenzoate, and polytetramethylene oxide-di-p-aminobenzoate; ethylene glycol, Pyrene glycol, diethylene glycol, trimethylene glycol, tetraethylene glycol, triethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 2,3-butanediol, 1,2-butanediol, 3-methyl-1,2-butanediol, 1,2-pentanediol, 1,4-pentanediol, 2,4-pentanediol, 2,3-dimethyltrimethylene glycol, tetramethylene glycol, 3-methyl-4,3-pentanediol, 3- Examples of polyhydric alcohol compounds include methyl-4,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,6-hexanediol, 1,5-hexanediol, 1,4-hexanediol, 2,5-hexanediol, 1,4-cyclohexanedimethanol, neopentyl glycol, glycerin, trimethylolpropane, trimethylolethane, trimethylolmethane, poly(oxytetramethylene) glycol, polyethylene glycol, and polypropylene glycol.The polyamine compound may have a hydroxyl group, and examples of such amine compounds include 2-hydroxyethylethylenediamine, 2-hydroxyethylpropylenediamine, di-2-hydroxyethylethylenediamine, di-2-hydroxyethylpropylenediamine, 2-hydroxypropylethylenediamine, di-2-hydroxypropylethylenediamine, etc. As the polyamine compound, a diamine compound is preferable, and it is more preferable to use, for example, 3,3'-dichloro-4,4'-diaminodiphenylmethane (methylenebis-o-chloroaniline) (hereinafter abbreviated as MOCA).

[0043] The polishing layer 4 can be formed by using a material to form hollow microspheres 4A, which have an outer shell and are hollow inside. The material of the hollow microspheres 4A may be a commercially available one, or may be one obtained by synthesis using a conventional method. The material of the outer shell of the hollow microspheres 4A is not particularly limited, and examples thereof include polyvinyl alcohol, polyvinylpyrrolidone, poly(meth)acrylic acid, polyacrylamide, polyethylene glycol, polyhydroxyether acrylate, maleic acid copolymer, polyethylene oxide, polyurethane, poly(meth)acrylonitrile, polyvinylidene chloride, polyvinyl chloride and organic silicone resins, and copolymers of two or more types of monomers constituting these resins. In addition, examples of commercially available hollow microspheres include, but are not limited to, Expancel series (trade name manufactured by Akzo Nobel), Matsumoto Microsphere (trade name manufactured by Matsumoto Yushi Co., Ltd.), and the like.

[0044] The shape of the hollow microspheres 4A is not particularly limited and may be, for example, spherical or nearly spherical. The average particle size of the hollow microspheres 4A is not particularly limited but is preferably 5 to 200 μm, more preferably 5 to 80 μm, further preferably 5 to 50 μm, and particularly preferably 5 to 35 μm. The average particle size can be measured by a laser diffraction particle size distribution analyzer (for example, Mastersizer 2000, manufactured by Spectris Co., Ltd.).

[0045] The material for the hollow microspheres 4A is added in an amount of preferably 0.1 to 10 parts by mass, more preferably 1 to 5 parts by mass, and even more preferably 1 to 3 parts by mass, based on 100 parts by mass of the urethane prepolymer.

[0046] In addition to the above components, conventionally used blowing agents may be used together with the hollow microspheres 4A within the range that does not impair the effects of the present invention, and a gas that is non-reactive with each of the above components may be blown in during the mixing step described below. Examples of the blowing agent include water and blowing agents mainly composed of hydrocarbons having 5 or 6 carbon atoms. Examples of the hydrocarbon include linear hydrocarbons such as n-pentane and n-hexane, and alicyclic hydrocarbons such as cyclopentane and cyclohexane.

[0047] <Mixing process> In the mixing step, the urethane bond-containing polyisocyanate compound (urethane prepolymer) obtained in the preparation step, additives, and curing agent are fed into a mixer and stirred and mixed. The mixing step is carried out in a state where the components are heated to a temperature at which the fluidity of each component can be ensured.

[0048] <Forming process> In the molding process, the mixture for molding prepared in the mixing process is poured into a rod-shaped mold preheated to 30 to 100°C for primary curing, and then heated at about 100 to 150°C for about 10 minutes to 5 hours for secondary curing to form a cured polyurethane resin (polyurethane resin molded body). At this time, the urethane prepolymer and the curing agent react to form a polyurethane resin, and the mixture hardens. If the viscosity of the urethane prepolymer is too high, the fluidity is poor and it becomes difficult to mix uniformly during mixing. If the temperature is increased to decrease the viscosity, the pot life is shortened, and mixing spots occur, resulting in variation in the size of the hollow microspheres 4A formed in the resulting foam. On the other hand, if the viscosity is too low, the bubbles move in the mixed liquid, making it difficult to form the hollow microspheres 4A dispersed uniformly in the resulting foam. For this reason, it is preferable to set the viscosity of the prepolymer in the range of 500 to 4000 mPa·s at a temperature of 50 to 80°C. This can be achieved, for example, by changing the molecular weight (degree of polymerization) of the prepolymer. The prepolymer is heated to about 50 to 80°C to be in a flowable state.

[0049] In the molding process, the mixture is reacted in a mold as necessary to form a foam. At this time, the prepolymer crosslinks and hardens due to the reaction between the prepolymer and the hardener. As this crosslinking and hardening progresses, the isocyanate groups of the prepolymer react with the water dispersed and diluted in the dispersion liquid, generating carbon dioxide. As the crosslinking and hardening progresses, the generated carbon dioxide does not escape to the outside, forming hollow microspheres 4A.

[0050] After obtaining the molded body, it is sliced ​​into sheets to form a plurality of polishing layers 4. A general slicing machine can be used for slicing. During slicing, the lower part of the polishing layer 4 is held, and the polishing layer 4 is sliced ​​to a predetermined thickness starting from the upper part. The sliced ​​thickness is set to, for example, a range of 1.3 to 2.5 mm. In the case of a foam molded in a 50 mm thick mold, for example, about 10 mm of the upper and lower parts of the foam are not used due to scratches, and 10 to 25 polishing layers 4 are formed from about 30 mm of the center. In the hardening and molding process, a foam is obtained in which hollow microspheres 4A are formed approximately uniformly inside.

[0051] Slurry retaining grooves and slurry discharge grooves are formed on the polishing surface of the obtained polishing layer 4. By performing cutting or the like on the polishing surface using a required cutter, grooves having any pitch, width, and depth can be formed.

[0052] Thereafter, a double-sided tape is attached to the surface of the polishing layer 4 opposite to the polishing surface of the polishing layer 4 obtained in this manner. There are no particular limitations on the double-sided tape, and any double-sided tape known in the art can be selected and used.

[0053] <Method of manufacturing the cushion layer 6> The cushion layer 6 is preferably made of an impregnated nonwoven fabric impregnated with a resin. Examples of the resin include polyurethanes such as polyurethane and polyurethane polyurea, acrylics such as polyacrylate and polyacrylonitrile, vinyls such as polyvinyl chloride, polyvinyl acetate and polyvinylidene fluoride, polysulfones such as polysulfone and polyethersulfone, acylated celluloses such as acetylated cellulose and butyrylated cellulose, polyamides and polystyrenes. The density of the nonwoven fabric before impregnation with the resin (web state) is preferably 0.3 g / cm. 3 More preferably, it is 0.1 to 0.25 g / cm 3 The density of the nonwoven fabric after resin impregnation is preferably 0.7 g / cm. 3 More preferably, it is 0.25 to 0.5 g / cm 3 The density of the nonwoven fabric before and after resin impregnation is equal to or less than the upper limit, so that the processing accuracy is improved. Furthermore, the density of the nonwoven fabric before and after resin impregnation is equal to or more than the lower limit, so that the penetration of the polishing slurry into the base layer 103 can be reduced. The adhesion rate of the resin to the nonwoven fabric is expressed as the weight of the adhered resin relative to the weight of the nonwoven fabric, and is preferably 40% by weight or more, and more preferably 50 to 100% by weight. The adhesion rate of the resin to the nonwoven fabric is equal to or less than the upper limit, so that the desired cushioning properties can be obtained.

[0054] <Joining process> In the bonding step, the formed polishing layer 4 and cushion layer 6 are bonded (bonded) with an adhesive layer 7. For example, an acrylic adhesive is used for the adhesive layer 7, and the adhesive layer 7 is formed to a thickness of 0.1 mm. That is, the acrylic adhesive is applied to the surface of the polishing layer 4 opposite the polishing surface to a substantially uniform thickness. The surface of the polishing layer 4 opposite the polishing surface and the surface of the cushion layer 6 are pressed against each other via the applied adhesive, and the polishing layer 4 and the cushion layer 6 are bonded with the adhesive layer 7. Then, after cutting into a desired shape such as a circle, an inspection is performed to confirm that there is no dirt or foreign matter attached, and the polishing pad 3 is completed. EXAMPLES

[0055] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0056] In each of the examples and comparative examples, unless otherwise specified, "parts" means "parts by mass".

[0057] In addition, the NCO equivalent is a value indicating the molecular weight of the prepolymer (PP) per NCO group, which is calculated by (mass (parts) of polyisocyanate compound + mass (parts) of polyol compound) / [(number of functional groups per molecule of polyisocyanate compound × mass (parts) of polyisocyanate compound / molecular weight of polyisocyanate compound)-(number of functional groups per molecule of polyol compound × mass (parts) of polyol compound / molecular weight of polyol compound)].

[0058] (About the polishing layer) 2.6 parts of unexpanded hollow bodies, the shell of which is made of acrylonitrile-vinylidene chloride copolymer and which contains isobutane gas in the shell, were added and mixed with 100 parts of isocyanate-terminated urethane prepolymer with an NCO equivalent of 460, which was made by reacting 2,4-tolylene diisocyanate (TDI), poly(oxytetramethylene) glycol (PTMG) and diethylene glycol (DEG), to obtain a mixed liquid. The resulting mixed liquid was charged into a first liquid tank and kept warm. Next, 25.5 parts of MOCA and 8.5 parts of polypropylene glycol (PPG) were added and mixed as hardeners separately from the first liquid, and kept warm in a second liquid tank. The liquids in the first liquid tank and the second liquid tank were each injected into a mixer equipped with two injection ports so that the R value, which represents the equivalent ratio of amino groups and hydroxyl groups present in the hardener to the terminal isocyanate groups in the prepolymer, was 0.90. The two injected liquids were mixed and stirred while being injected into a preheated mold of a molding machine, then the mold was clamped and heated for 30 minutes for primary curing. The primarily cured molded product was demolded and then secondary cured in an oven at 110°C for 4 hours to obtain a urethane molded product. The obtained urethane molded product was allowed to cool to 25°C, and then heated again in an oven at 120°C for 5 hours, before being sliced ​​to a thickness of 1.3 mm to obtain an abrasive layer.

[0059] (About the cushion layer) Nonwoven fabric made of polyester fibers (density: 0.216 g / cm 3 ) was immersed in a urethane resin solution (manufactured by DIC Corporation, product name "C1367"). After immersion, the resin solution was squeezed out using a mangle roller capable of applying pressure between a pair of rollers, and the nonwoven fabric was impregnated with the resin solution approximately uniformly. Next, the nonwoven fabric was immersed in a coagulating liquid made of water at room temperature to coagulate and regenerate the impregnated resin, thereby obtaining a resin-impregnated nonwoven fabric. Thereafter, the resin-impregnated nonwoven fabric was taken out of the coagulating liquid, and further immersed in a cleaning liquid made of water to remove N,N-dimethylformamide (DMF) in the resin, and then dried. After drying, the surface skin layer was removed by buffing treatment to prepare a cushion layer. The resin adhesion rate of the cushion layer was 55%, and the thickness was 1.30 mm.

[0060] (Physical property evaluation) The physical properties of the polishing layer and the cushion layer used in the polishing pad were measured. The Shore D hardness was determined from the indentation depth of the indenter pressed against the surface of the test piece via a spring, in accordance with the Japanese Industrial Standards (JIS K 6253). Similarly, the Shore A hardness was determined from the indentation depth of the indenter pressed against the surface of the test piece via a spring, in accordance with the Japanese Industrial Standards (JIS K 7311). The compressive modulus was determined using a Shopper-type thickness measuring device (pressure surface: circular with a diameter of 1 cm) in accordance with the Japanese Industrial Standards (JIS L 1021). Specifically, the thickness t0 was measured after applying pressure with the initial load for 30 seconds, and then the thickness t1 was measured after leaving it under the final pressure for 5 minutes. After removing all loads and leaving it for 5 minutes, the thickness t0' was measured after applying pressure with the initial load for 30 seconds again. The compressive modulus was calculated as compressive modulus (%) = (t0'-t1) / (t0-t1) x 100. At this time, the initial load was 100 g / cm 2 , final pressure is 1120g / cm 2 It was.

[0061] The physical properties of the polishing layer and cushion layer used are shown in Tables 1 and 2. [Table 1]

[0062] [Table 2]

[0063] Examples and Comparative Examples The polishing layer and the cushion layer were joined with a 0.1 mm thick double-sided tape (a PET substrate with an adhesive layer made of an acrylic resin on both sides), and the cushion layer and the adhesive layer were attached to the opposite side of the double-sided tape to produce a polishing pad. The polishing pad thus obtained had a composite groove of a slurry discharge groove and a slurry holding groove as shown in Table 3 formed on the polishing surface thereof, which were used as Examples 1 to 4 and Comparative Examples 1 to 3. Here, the groove pitch of each groove is shown as γ in FIG. 9, the groove width is shown as β in FIG. 9, the groove depth is shown as the depth of the deepest part from the polishing surface to the bottom surface of the groove in FIG. 8, and the cross-sectional shape is shown as the cross-sectional shape of the groove as in FIG. 8. The groove area ratio indicates the ratio of the area of ​​the grooves to the area of ​​the polished surface, and was calculated by the following formula. For grating grooves: (1-land width 2 / groove pitch 2 ) x 100 For concentric grooves: groove width / groove pitch For through holes: (1cm 2 (Number of through holes per unit) x (area of ​​through holes (cm 2 ))×100 (In Comparative Example 1, the through holes were 5 per cm 2 The diameter of each through hole was 2 mm, so the groove area ratio was 15.7%. Furthermore, the groove volume ratio (discharge / retention) is the volume ratio of the slurry discharge grooves to the slurry retention grooves calculated from the area ratio, groove depth and cross-sectional shape calculated above.

[0064] [Table 3] (Polishing performance evaluation) Polishing was carried out under the following polishing conditions for the polishing pads of the examples and comparative examples. The polishing rate (RR) was measured at 121 points in diameter during polishing. The polishing rate profile of the entire polished object of Comparative Example 1 is shown in FIG. 4, the pressure response of the edge portion of the polished object 8 of Comparative Example 1 is shown in FIG. 5, the polishing rate profile of the entire polished object of Example 1 is shown in FIG. 10, and the pressure response of the edge portion of the polished object of Example 1 is shown in FIG. 11. The inside of the radius of 140 mm was measured at a pitch of 2.5 mm, and the outside was measured at a pitch of 1 mm. The pressure response was expressed as the rate of change in the edge rate ratio (the polishing rate of the edge portion (145 mm to 149 mm from the center of the polished object) divided by the average polishing rate of the portion 100 mm to 140 mm from the center of the polished object, shown on the vertical axis of FIGS. 5 to 11) when the pressure applied to the retainer ring was increased by 10% and 20% compared to the normal pressure.

[0065] (polishing conditions) Polishing machine used: F-REX300 (manufactured by Ebara Corporation) Abrasive temperature: 20℃ Polishing platen rotation speed: 70 rpm Polishing head rotation speed: 71 rpm Grinding pressure: 3.5psi Polishing slurry: Cabot Microelectronics Corporation, product name: SS25 Polishing slurry flow rate: 200ml / min Polishing time: 60 seconds Workpiece: Silicon wafer with TEOS (Tetra Ethyl Ortho Silicate)

[0066] The polishing results of each polishing pad of the examples and comparative examples are shown in Table 4. The "edge rate" of the polishing results was calculated by dividing the polishing rate of the edgemost part of the workpiece (part 149 mm from the center) by the average of the polishing rates of parts 100 to 140 mm from the center. The pressure response is shown as the rate of change in the edgemost rate when the pressure applied to the retainer ring is increased by 10% and 20% from the normal pressure (corresponding to Ref in Figures 5 and 11).

[0067] [Table 4]

[0068] As shown in Figures 4 to 5 and Table 4, in the polishing pad of Comparative Example 1, in which the groove volume ratio (discharge / retention) is low at 0.193, the rate of the most edge portion is large at 1.68, and sagging of the edge is confirmed, and the responsiveness when the pressure of the retaining ring is increased by 10% and 20% is low at 4.2% and 8.3%, respectively, making it difficult to adjust the edge profile by increasing the pressure of the retaining ring. A similar tendency was observed in Comparative Example 2, in which the groove volume ratio (discharge / retention) is low at 0.389. In addition, in Comparative Example 2, in which the groove volume ratio (discharge / retention) is high at 1.203, the proportion of the slurry discharge grooves is too large, resulting in an insufficient polishing rate for the entire workpiece. On the other hand, as shown in Figures 6 to 7 and Table 3, in the polishing pad of Example 1 in which the groove volume ratio (discharge / retention) was 0.777, the rate at the outermost edge was 1.28, suppressing edge sagging, and the responsiveness when the retainer ring pressure was increased by 10% and 20%, respectively, was high at 9.4% and 17.2%, making it possible to further suppress edge sagging and adjust the edge profile by increasing the retainer ring pressure. In other examples in which the groove volume ratio (discharge / retention), groove width ratio (discharge / retention), and groove pitch ratio (discharge / retention) were within the specified range, the increase in the polishing rate at the outermost edge (edge ​​sagging) was suppressed, high pressure responsiveness was exhibited, and a good edge profile was obtained. [Industrial Applicability]

[0069] The present invention provides a polishing pad that enables improvement of edge sagging without changing the physical properties or cell structure of the polishing layer, and therefore contributes to the manufacture and sale of polishing pads, and thus has industrial applicability.

[0070] Explanation of symbols 1 Polishing equipment 3 Polishing Pads 4 Polishing layer 4A Hollow microspheres 5 grooves 5A Slurry retention groove 5B Slurry discharge ditch 6 Cushioning Layer 7 Adhesive layer 8 Object to be polished 8a End droop 9. Slurry 10 Polishing plate 11 Foundation 16 Holding Plate

Claims

1. A polishing pad having a polishing layer having a polishing surface for polishing an object to be polished, the polishing surface is provided with a slurry retaining groove having a shape for retaining a slurry, and a slurry discharge groove having a shape for discharging the slurry; a ratio of a volume of the slurry retaining groove to a volume of the slurry discharge groove (discharge groove volume / retaining groove volume) of 0.688 to 0.918; the polishing layer comprises hollow microspheres; the hollow microspheres are dispersed in the polishing layer; The polishing pad has a polishing rate of 1.41 or less at the outermost edge under the following polishing conditions: (polishing conditions) Polishing machine used: F-REX300 (manufactured by Ebara Corporation), Abrasive temperature: 20°C, Polishing platen rotation speed: 70 rpm, Polishing head rotation speed: 71 rpm, Grinding pressure: 3.5 psi, Polishing slurry: Product name: SS25, manufactured by Cabot Microelectronics Corporation Polishing slurry flow rate: 200 ml / min, Polishing time: 60 seconds, Polished object: silicon wafer with TEOS (Tetra Ethyl Ortho Silicate), radius 150 mm Edge portion polishing rate: A value obtained by dividing the edge portion polishing rate of the workpiece by the average polishing rate in a portion 100 to 140 mm from the center.

2. 2. The polishing pad according to claim 1, wherein the groove width ratio (discharge / retention) between the slurry retaining groove and the slurry discharge groove is 1.5 to 7.

5.

3. 3. The polishing pad according to claim 1, wherein the groove pitch ratio (discharge / retention) between the slurry retaining grooves and the slurry discharge grooves is 4.5 to 15.

4. 4. The polishing pad according to claim 1, wherein hollow microspheres are dispersed on the polishing surface.

Citation Information

Patent Citations

  • Polishing pad, polishing method, semiconductor device and manufacturing method thereof

    JP2006156876A

  • Polishing pad

    JP2011177884A

  • Polishing pad and method of polishing semiconductor wafer

    JP2012000714A

  • Polishing pad

    JP2013035108A

  • Polishing pad

    JP2016190313A